A novel 27-bp indel in the intron region of the YBX3 gene is associated with growth traits in chickens. Issue 5 (3rd September 2022) - Li, T.; Qin, P.; Chen, B.; Niu, X.; Wang, Y.; Niu, Y.; Wei, C.; Hou, D.; Ma, H.; Han, R.; Li, H.; Liu, X.; et al.
ABSTRACT: 1. The DNA/RNA binding protein YBX3 is associated with gene transcription, DNA repair, and the progression of various diseases and is highly conserved from bacteria to humans. 2. The following experiment found a 27-bp insertion/deletion polymorphism in the intron region of the YBX3 gene through resequencing. In cross-designed, F2 resource groups, the indel was significantly associated with broiler weight and body size at 0, 2, 4, 6, 8, 10 and 12 weeks of age and several other traits (semi evisceration weight (SEW), evisceration weight (EW), semi evisceration rate (SER), evisceration rate (ER), head weight (HW), claw weight (CLW), wing weight (DWW), gizzard weight (GW), pancreas weight (PW), chest muscle weight (CMW), leg weight (LW), leg muscle weight (LMW), shedding weight (SW), carcase weight (CW) and pectoral area (PA)) (P < 0.05). 3. The insertion-insertion (II) genotype was significantly associated with the greatest growth traits and carcase traits, whereas the values associated with the insertion-deletion (ID) genotype were the lowest in the F2 reciprocal cross chickens. 4. The mutation sites were genotyped in 3611 individuals from 13 different chicken breeds and cross-designed F2 resource groups. The II genotype is the most important in commercial broilers, and the I allele frequency observed in these breeds was relatively high. However, there is still considerable potential in breeding dual-purpose chickens and commercial laying hens. 5. The mRNA expression of the YBX3 gene in tissues from different breeds and developmental stages demonstrated that the 27-bp indel may affect the entire development process of poultry by affecting muscle development. These findings are beneficial for elucidating the function of the YBX3 gene and facilitating enhanced production in the chicken industry.